IL-6 blockers in systemic onset juvenile idiopathic arthritis. (January 2016) - Barone, Patrizia; Pignataro, Rossana; Garozzo, Maria Teresa; Leonardi, Salvatore
IL-6 has a key role in the pathogenesis, clinical manifestations and activity of Systemic Onset Idiopathic Arthritis (sJIA). Tocilizumab (TCZ), the first humanized antihuman IL-6 receptor antibody, inhibits the activity of IL-6. In this review, we summarize the main studies performed, to date, about the use of TCZ in children affected by sJIA refractory to conventional treatment. Nowadays TCZ can be used, alone or in association with Metotrexate, in children older than 2 years. Its use in children younger than 2 years is being investigated. Further study about its use in sJIA and other type of idiopathic arthritis should be done.